"On-command" dissolvable tympanostomy tube in the chinchilla model: A proof of concept. (October 2017) - Wiedermann, Joshua P.; Mai, Johnny P.; Dumont, Matthieu; Jenkins, Audrey; Cleary, Kevin; Reilly, Brian K.
Abstract: Objectives: To prove the concept that a dissolvable "on-command" tympanostomy tube placed into the tympanic membrane of a chinchilla can dissolve when a benign solution is applied and result in a well healed tympanic membrane without histologic evidence of injury. Study design: Prospective Randomized Single-Subject Controlled Trial. Methods: Prototype tympanostomy tubes were fabricated from poly(butyl methacrylate- co -(2-dimethylaminoethyl) methacrylate- co - methyl methacrylate) (PBM). " In vitro " dissolution studies were performed with applications of the benign chemical, hydrogen peroxide (HP). PBM tubes were placed into ten chinchilla tympanic membranes matched with standard plastic tubes placed into the contralateral side. All 20 tubes were exposed to HP for 21 days with serial endoscopic examinations. In vitro PBM tubes were weighed before and after interventions and compared to control tubes. In vivo photo documentation was used to show progression of dissolution and histologic slides were obtained to show the effect of the PBM on surrounding tissues. Results: Compared to control tubes, all those exposed to hydrogen peroxide had a statistically significant reduction in weight (p < 0.01). After placement into the tympanic membrane of chinchillas, all PBM tubes dissolved within 21 days of hydrogen peroxide treatment leaving behind histologically normal, intact tympanic membranes. Conclusion: Our PBM tubes dissolve "on-command" in a chinchilla model when exposed to treatment with a benign chemical. Dissolvable "on-command" tympanostomy tubes may reduce significant complications related to pediatric tympanostomy tube use.